Low contrast media volume in pre-TAVI CT examinations - Kok, Madeleine (Eur Radiol, 2015)
PURPOSE: To evaluate image quality using reduced contrast media (CM) volume in pre-TAVI assessment. METHODS: Forty-seven consecutive patients referred for pre-TAVI examination were evaluated. Patients were divided into two groups: group 1 BMI < 28 kg/m(2) (n = 29); and group 2 BMI > 28 kg/m(2) (n = 18). Patients received a combined scan protocol: retrospective ECG-gated helical CTA of the aortic root (80kVp) followed by a high-pitch spiral CTA (group 1: 70 kV; group 2: 80 kVp) from aortic arch to femoral arteries. All patients received one bolus of CM (300 mgI/ml): group 1: volume = 40 ml; flow rate = 3 ml/s, group 2: volume = 53 ml; flow rate = 4 ml/s. Attenuation values (HU) and contrast-to-noise ratio (CNR) were measured at the levels of the aortic root (helical) and peripheral arteries (high-pitch). Diagnostic image quality was considered sufficient at attenuation values > 250HU and CNR > 10. RESULTS: Diagnostic image quality for TAVI measurements was obtained in 46 patients. Mean attenuation values and CNR (HU ± SD) at the aortic root (helical) were: group 1: 381 ± 65HU and 13 ± 8; group 2: 442 ± 68HU and 10 ± 5. At the peripheral arteries (high-pitch), mean values were: group 1: 430 ± 117HU and 11 ± 6; group 2: 389 ± 102HU and 13 ± 6. CONCLUSION: CM volume can be substantially reduced using low kVp protocols, while maintaining sufficient image quality for the evaluation of aortic root and peripheral access sites. KEY POINTS: • Image quality could be maintained using low kVp scan protocols. • Low kVp protocols reduce contrast media volume by 34–67 %. • Less contrast media volume lowers the risk of contrast-induced nephropathy.